2015
DOI: 10.1007/s10585-015-9741-2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular fibronectin 1 promotes VEGF-C expression, lymphangiogenesis and lymph node metastasis associated with human oral squamous cell carcinoma

Abstract: Lymph node metastasis (LNM) is associated with poor survival in patients with oral squamous cell carcinoma (OSCC). Vascular endothelial growth factor-C (VEGF-C) is thought to be responsible for increased lymphangiogenesis and LNM. Understanding of the mechanism by which VEGF-C expression is regulated in OSCC is thus important to design logic therapeutic interventions. We showed that inoculation of the SAS human OSCC cells expressing the venus GFP (V-SAS cells) into the tongue in nude mice developed LNM. V-SAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 56 publications
2
43
0
Order By: Relevance
“…As an EMT marker, fibronectin is involved in cell adhesion and migration, including embryogenesis,17 wound healing,18 blood coagulation,19 osteogenesis,20 and metastasis 21,22. EMT is a process involved in embryonic development, during which cells lose their epithelial features and adopt characteristics of mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…As an EMT marker, fibronectin is involved in cell adhesion and migration, including embryogenesis,17 wound healing,18 blood coagulation,19 osteogenesis,20 and metastasis 21,22. EMT is a process involved in embryonic development, during which cells lose their epithelial features and adopt characteristics of mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin 1 ( FN1 ) mediates a wide variety of cellular interactions with the ECM, and is involved in cell adhesion, migration processes, and metastasis . Moreover, it is reported that altered expression of fibronectin 1 exists in several squamous cell carcinomas, including ESCC, head and neck squamous cell carcinoma, and oral squamous cell carcinoma . The derivation of these three genes predictive of clinical outcome in patients with ESCC may reveal PPI anticancer targets for the development of therapy for esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Attention has particularly been paid to the fact that, with a few exceptions [101][102][103][104][105][106], the role of FN expression in tumor cells was primarily thought of as a tumor suppressor prior to the 1990s, yet later the consensus switched to its role being a metastatic promoter as aforementioned. It remains obscure why there are such two cut-off phases as to the different time periods for the obviously conflicting mainstream conceptions regarding the role of FN in tumor progression.…”
Section: Reconciliation Of the Paradoxical Role Of Fn In Cancermentioning
confidence: 99%